The Relationship between Happiness and Mental Health of Chittagong University Students (Chittagong University Journal of Biological Sciences, 2025)
This study examined the relationship between happiness and mental health among 300 undergraduate students (150 males, 150 females) at the University of Chittagong. The participants were selected conveniently.  Participants completed the Oxford Happiness Questionnaire (OHQ) and the General Health Questionnaire-28 (GHQ-28). The Oxford Happiness Questionnaire was originally developed by Argyle and Hills (2002) and translated and adapted into Bangla by Uddin and Haque (2008). The General Health Questionnaire-28 was originally developed by Goldberg and Williams (1988) and translated and adapted into Bangla by Banoo (2001). Results revealed a relatively high average happiness score (M = 113.76) alongside moderate levels of psychological distress (M = 28.30). Correlation analysis indicated a significant negative relationship between happiness and overall mental health problems (r = –.65, p < .01), supporting previous findings from both local and international research. The results suggest that mental health and happiness are deeply interconnected and should be addressed together. Therefore, university administrations and policymakers should consider incorporating well-being initiatives-such as mindfulness, gratitude exercises, and peer support programs into student services. Such efforts could not only improve mental health outcomes but also foster a more fulfilling and productive academic environment.Chittagong Univ. J. B. Sci. Vol. 13 (1&2): 68-76, 2025